Empirical Mathematical Model of Multiple Interaction Cracks - Che Ariffin, Muhammad Najmi; Awang, Muhammad Khairudin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
As Stress Intensity Factors (SIF) may be used to measure the fracture force of the faulty structure quantitatively, the engineering application of fracture mechanics relies largely on knowledge of stress intensity factors. Many researcher methods have so far been proposed to measure stress intensity factors. Over the past few years, because of their reducing structural integrity, the issue of extended operations of aging aircraft structures is becoming pressing. Therefore, this study aims to investigate the SIF for multiple cracks growth by using software such Microsoft excel. It detailed about the existing study of multiple cracks and how to formulate the empirical mathematical model to predict the SIF. The findings of relationship between independent variable and dependent variable of multiple cracks with different load types. The parameters of the model are a/D and a/b which are crack depth ratio and cracks aspect ratio respectively. By using different cracks shapes of 0.1,0.2,0.3 and 0.4. For a/b, the range are from 0.2 and 1.2 with the increment of 0.2. The variable of c/l is 0.005, 0.01, 0.02,0.04, 0.08,0.16, 0.32. In conclusion, the equation has been made for SIF. The objective was achieved with seven equations are shown in this thesis from different C/L, a/D, a/b values